Profile of breast milk donors from a human milk bank from a south Brazil university hospital (Research, Society and Development, 2022)
Objective: to identify the profile according to the sociodemographic and perinatal variables of breast milk donors from an human bank milk in southern Brazil. Methods: cross-sectional, descriptive study, carried out based on 200 records of women donors in 2018. The data collected were tabulated and subsequently analyzed using descriptive statistics. Results: It was identified that the donors were over 25 years old (57.5%), high school (42.5%) and had some professional activity (50.5%). Most held their prenatal consultations in public institutions (64.5%), were multiparous (58.5%), with babies born at term (58%), cesarean section (59.5%) with weight appropriate to the be born (64.5%). They had no experience of previous pregnancy with breastfeeding (56.5%) and received guidance on breastfeeding in prenatal care (64.5%). With regard to information about the HMB, most donors received this information from college hospital health professionals (49,5%). Conclusion: In view of the benefits brought by the HMB, it is extremely important to know the characteristics of human milk donors, which may guide managers in the implementation of intervention strategies aimed at educational actions and promotion of breastfeeding. These policies may increase the number of donors and the volume of milk collected.